Die Generierung von künstlichen Keimzellen Medizinische, rechtliche und ethische Aspekte - Mall, Eva; Schlatt, Stefan; Gassner, Ulrich M.; Spranger, Tade Matthias; Ranisch, Robert; Rolfes, Vasilija (Ethik in den Biowissenschaften, 2023)
So far, it has not been possible to generate human sperm and egg cells from pluripotent stem cells. However, completion of in vitro gametogenesis (IVG) is expected in the near future because progenitor cells from human gamete have already been generated. Gametes produced this way could fundamentally expand both the understanding of early human development and reproductive treatments for infertility. This expert report provides basic medical information on the development of human gametes, considers relevant legal standards and key ethical issues such as balancing genetic parenthood against potential harms resulting from IVG. With contributions by Ulrich M. Gassner | Eva Mall | Stefan Schlatt | Tade Matthias Spranger | Robert Ranisch | Vasilija Rolfes